THE STUDY OF RISK FACTORS FOR THE DEVELOPMENT OF CARIES IN PUPILS OF THE FIRST GRADES IN SECONDARY SCHOOLS (British Journal of Global Ecology and Sustainable Development, 2024)
Children's caries is a special form of pathology that has a complex, diverse, interacting multifactorial nature. This article examines the risk factors for caries among primary school children, provides the results of assessing the level of their theoretical knowledge on the issue under study, as well as data on the food habits and oral hygiene of respondents.